Penentu Profitabilitas Bank Syariah: Kajian Nisbah Bagi Hasil dan Murabahah - Irma Setyawati; Beureukat Beureukat (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
The purpose of this research is to analyze how the profit sharing ratio and profit margin in murabaha can affect the return on assets of Islamic banks in Indonesia. The method used in this research is quantitative descriptive, the data used is secondary data by taking data from Islamic bank financial reports for the period 2019 – 2021. The population of Islamic banks is 14 banks, then data is taken from 3 banks using a purposive sampling technique. In this study it was found that profit sharing ratios and profit margins in murabahah transactions are important in increasing the profitability of Islamic banks in Indonesia. High profit sharing for Islamic banks will increase bank profits, but profitable profit sharing ratios for Islamic banks will make customers reluctant to deposit their funds in Islamic banks which will reduce profits. Thus the size of the profit sharing ratio between the customer and the bank must comply with the principles of fairness and equity. Likewise, high profit margins charged to customers will make customers look for other financing alternatives outside of Islamic banks